THE REPRESENTATION OF LABOR IN THE ONE-DIMENSIONAL SOCIETY: AN ANALYSIS OF “WE’RE ALL SAMARCO” ON A SOCIAL NETWORK - Souza1, Rosália Beber de; Baet, Odemir Vieira; Cappelle, Mônica Carvalho Alves; Brito, Mozar José de (Cadernos de Linguagem e Sociedade, 2018)
The article discusses the one-dimensional labor society by grounding itself on the reflections of Herbert Marcuse. It also seeks to establish a connection between the concepts presented by the author, Bhaskar’s Critical Realism, and Fairclough’s Critical Discourse Analysis. Through a theoretical and empirical study, we are discussing the contemporary understanding of labor built by discourses that were conveyed on Facebook in defense of the mining company Samarco after the accident in the city of Mariana (Minas Gerais, Brazil). Using Critical Discourse Analysis as both the theoretical and methodological support to this study, we are sticking to the representational meaning of the social actors involved, emphasizing the following categories: Social Representation, Interdiscursivity, and Lexical Choice. According to the analyzed discourses, Samarco is actively represented as a “savior” to the population, which, in turn, is portrayed as being passive and dependent on the company due to the necessity of keeping of their jobs.